Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physrevb.95.024413
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent first-order reversal curve measurements on unusually hard magnetic low-temperature phase of MnBi

Abstract: We have performed first-order reversal curve (FORC) measurements to investigate the irreversible magnetization processes in the low-temperature phase of MnBi. Using temperature-dependent FORC analysis, we are able to provide a clear insight into the effects of microstructural parameters such as grain diameter, shape, and surface composition on the coercivity of nucleation hardened permanent magnet MnBi. FORC diagrams of MnBi show a unique broadening and narrowing of the coercive field distribution with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…FORC has been successfully utilized to study an extensive amount of different magnetic systems. Whether for magnetic particles in geologic compounds [4][5][6][7], permanent magnet research [8][9][10], magnetic temperature dependence [11][12][13], the study of nanowires [14][15][16][17][18], or nanostructured dot and antidot systems [19][20][21], first-order reversal curves have a broad range of applications. It has been shown that FORC can also be extended to even more sophisticated methods like second-order reversal curve (SORC) [22], or temperature FORC [23].…”
Section: Introductionmentioning
confidence: 99%
“…FORC has been successfully utilized to study an extensive amount of different magnetic systems. Whether for magnetic particles in geologic compounds [4][5][6][7], permanent magnet research [8][9][10], magnetic temperature dependence [11][12][13], the study of nanowires [14][15][16][17][18], or nanostructured dot and antidot systems [19][20][21], first-order reversal curves have a broad range of applications. It has been shown that FORC can also be extended to even more sophisticated methods like second-order reversal curve (SORC) [22], or temperature FORC [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different candidates, Mn-and Fe-based alloys [7,8,9] are meeting the abundance criterion, while Co-based alloys [10,11,12] benefit from the high intrinsic anisotropy of cobalt.…”
Section: Introductionmentioning
confidence: 99%
“…This limit equals the ideal nucleation field H N associated with two intrinsic parameters of material K u and M s , H N = 2K u /M s [12]. For MnBi, by using the approximation K u ≈ K 1 + 2K 2 [8], M s = 81.3 emu/g and ρ = 9.042 g/cm 3 , this limit, at room temperature is estimated approximately H N = 39 kOe Depending on the methods of estimation of K u , H N suffers a great fluctuation, up to 56 kOe as announcedin [13]. Particularly, this upper limit of coercivity should be for a dense MnBi bulk magnet owning an ideal microstructure with non-defected, non-interacted, single-domain-sized, and perfectly aligned grains assembly.…”
Section: Ii2 Coercivitymentioning
confidence: 99%
“…4. The scheme of variation of coercivity H c versus reduction of grain size D for ferromagnetic solids [13].…”
Section: Critical Diammentioning
confidence: 99%